2012
DOI: 10.15208/mhsj.2012.40
|View full text |Cite
|
Sign up to set email alerts
|

Immune status parameters significance in pregnancy interruption on type of missed abortion in first trimester

Abstract: The paper explores the system immunity role of the first trimester missed abortion using the study of maintenance in populations and subpopulations of lymphocytes in the peripheral blood. Immune system disorders might cause self-regulation failure and immune response change. Recognition and removal of these disorders allow successful performing of implantation and increasing the probability for the pregnancy carriage. Survey of certain systemic immunity indicators dynamics and their contribution into the misse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Studies have indicated that the causes of MA are multiple and complex, including abnormalities in chromosome number and structure (7,8), immune dysfunction (9,10), endocrine dysfunction (11), abnormal intrauterine environment (12), hereditary thrombophilia (13), systemic infectious diseases (14,15) and environmental factors (3). However, in ~50% of affected patients, the reason for the occurrence of MA and the associated pathogenesis remain elusive (16).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that the causes of MA are multiple and complex, including abnormalities in chromosome number and structure (7,8), immune dysfunction (9,10), endocrine dysfunction (11), abnormal intrauterine environment (12), hereditary thrombophilia (13), systemic infectious diseases (14,15) and environmental factors (3). However, in ~50% of affected patients, the reason for the occurrence of MA and the associated pathogenesis remain elusive (16).…”
Section: Introductionmentioning
confidence: 99%